Application Of Project Based Learning Models To Improve Mathematics Learning Results Elementary School Students For Class 2 - Isnaeni Isnaeni (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve mathematics learning outcomes for students in grade II elementary schools with the Project Based Learning (PjBL) learning model by making projects in the form of nail boards in groups. The research conducted was a Classroom Action Research (CAR) in three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. In the first cycle, the students who completed the evaluation were 37,5%. In the second cycle, students who completed the evaluation were 81,25%. In cycle III, students who completed after evaluating were 93,75%. These results indicate that the Project Based Learning (PjBL) learning model by making projects in the form of nailed boards in groups can improve mathematics learning outcomes for Class II students at SDN 1 Randegan.